Museum Fatigue: Spatial Design Narrative Strategies of the Mawangdui Han Tomb - Jingwen Miao; Azizi Bahauddin; Jie Feng (Buildings)
Museum fatigue refers to the physical and psychological fatigue that visitors experience when visiting exhibitions due to information overload, dense display, or monotonous space design. This study takes Mawangdui Han Tomb as an example, draws on Lefebvre’s spatial triad theory, and realizes the transformation of cultural connotation from tomb space into museum space by analyzing perceived space, conceived space, and lived space. This transformation process also proposes a spatial design narrative strategy for this study to solve the problem of museum fatigue. This qualitative study uses ethnography to understand the Taoist and ritual-influenced tomb culture of the Mawangdui Han Tombs, followed by a phenomenological analysis of the museum (lived space). The research results show that a reasonable spatial layout, coherent narrative clues, and a multi-sensory interactive experience significantly improve audience concentration and reduce fatigue. This study provides practical design suggestions for future historical and cultural exhibitions.